2015
DOI: 10.3109/14767058.2015.1064103
|View full text |Cite
|
Sign up to set email alerts
|

Placenta accreta: diagnosis, management and the molecular biology of the morbidly adherent placenta

Abstract: Placenta accreta is now the chief cause of postpartum hemorrhage resulting in maternal and neonatal morbidity. Prenatal diagnosis decreases blood loss at delivery and intra and post-partum complications. Ultrasound is critical for diagnosis and MRI is a complementary tool when the diagnosis is uncertain. Peripartum hysterectomy has been the standard of therapy but conservative management is increasingly being used. The etiology of accreta is due to a deficiency of maternal decidua resulting in placental invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 31 publications
1
52
0
5
Order By: Relevance
“…Although modifying clinical decision making based on maternal variables seems reasonable, there is not consistency as to what maternal characteristics, maternal history, and labor and birth events change third‐stage management. It is reassuring, given that histories of placenta accreta or excessive uterine bleeding are risk factors for postpartum hemorrhage, that a large percentage of all participants reported these conditions would change their third‐stage management no matter what other variables were present and that this response was similar between midwives and physicians. However, of note, some participants also reported that a history of placenta accreta (4.3%) and excessive uterine bleeding (5.8%) would have no effect on their management of the third stage of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Although modifying clinical decision making based on maternal variables seems reasonable, there is not consistency as to what maternal characteristics, maternal history, and labor and birth events change third‐stage management. It is reassuring, given that histories of placenta accreta or excessive uterine bleeding are risk factors for postpartum hemorrhage, that a large percentage of all participants reported these conditions would change their third‐stage management no matter what other variables were present and that this response was similar between midwives and physicians. However, of note, some participants also reported that a history of placenta accreta (4.3%) and excessive uterine bleeding (5.8%) would have no effect on their management of the third stage of labor.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is that anti‐invasive factors, that are antagonist to matrix metalloproteinases or are activator of tissue inhibitor of metalloproteinases secreted by the decidua, are deficient in areas of decreased decidualization . Another possibility, is an imbalance in the paracrine/autocrine regulation between the deficient decidualized endometrium and the invasive trophoblasts .…”
Section: Etiopathogenesismentioning
confidence: 99%
“…MRI may be done for confirmation of placental adherent syndromes. 3 Thus, need for a good preoperative workup and more conservative approach to decrease morbidity and mortality associated with it. Here, we describe a case of placenta percreta successfully managed conservatively.…”
Section: Introductionmentioning
confidence: 99%